Modulating the vascular behavior of metastatic breast cancer cells by curcumin treatment - Palange, Anna Lisa; Di Mascolo, Daniele; Singh, Jaykrishna; De Franceschi, Maria Serena; Carallo, Claudio; Gnasso, Agostino; Decuzzi, Paolo (Frontiers in Oncology, 2012)
The spreading of tumor cells to secondary sites (tumor metastasis) is a complex process that involves multiple, sequential steps. Vascular adhesion and extravasation of circulating tumor cells (CTCs) is one, critical step. Curcumin, a natural compound extracted from Curcuma longa, is known to have anti-tumoral, anti-proliferative, anti-inflammatory properties and affect the expression of cell adhesion molecules, mostly by targeting the NF-κB transcription factor. Here, upon treatment with Curcumin, the vascular behavior of three different estrogen receptor negative (ER–) breast adenocarcinoma cell lines (SK-BR-3, MDA-MB-231, MDA-MB-468) is analyzed using a microfluidic system. First, the dose response to curcumin is characterized at 24, 48 and 72h using a XTT assay. For all three cell lines, an IC50 larger than 20 µM is observed at 72 h; whereas no significant reduction in cell viability is detected for curcumin concentrations up to 10 µM. Upon 24 h treatment at 10 µM of curcumin, SK-BR3 and MDA-MB-231 cells show a decrease in adhesion propensity of 40% (p = 0.02) and 47% (p = 0.001), respectively. No significant change is documented for the less metastatic MDA-MB-468 cells. All three treated cell lines show a 20% increase in rolling velocity from 48.3 to 58.7 µm/s in SK-BR-3, from 64.1 to 73.77 µm/s in MDA-MB-231 and from 57.5 to 74.4 µm/s in MDA-MB-468. Collectively, these results suggest that mild curcumin treatments could limit the metastatic potential of these adenocarcinoma cell lines, possibly by altering the expression of adhesion molecules, and the organization and stiffness of the cell cytoskeleton. Future studies will elucidate the biophysical mechanisms regulating this curcumin-induced behavior and further explore the clinical relevance of these findings.